Consciousness and meaning selected essays - Loar, Brian (Oxford University Press, 2017)
One of the most important problems of modern philosophy concerns the place of subjectivity in a purely physical universe. Brian Loar was a major contributor to the discussion of this problem for over four decades. This volume brings together his most important and influential essays in the philosophy of language and of mind
This edition previously issued in print: 2017
Keywords: Consciousness; Meaning (Philosophy); Sprachphysiologie; Philosophy of Mind; Aufsatzsammlung